Comparative Study for Replacing Dry Cooling Tower Instead of Wet Cooling Tower in Oil Refineries - Hoseinzadeh Hesas, Roozbeh; Sharifzadeh Baei, Mazyar; Hossein Tarighaleslami, Amir; Younessi Sinaki, Soroush (Asian Journal of Chemistry, 2013)
In cooling towers, heat and mass transfer occur simultaneously to cool water in the vicinity of air. Hence, the significant transfer of air and water to create moist air from the process cycle casualties is removed. The main goal of this research is to economical comparative study of total replacing dry cooling towers instead of wet cooling towers to reduce makeup water cost of cooling water system of the oil refinery. In order to review the definition of an objective function for a Trade-off between construction cost, installation and operation dry cooling tower and reduce the cost of wet cooling tower make-up water is more. Results obtained from studies in the sample case study objective function, the Tabriz refinery cooling towers were selected, expresses that according to dry bulb limitation it is practical to replace dry cooling towers just in 67 % days of year and the replacing cost for this days is 3,573,000.00 US and the makeup water saving cost during this days is 643,200.00 US. It is suggested that there is no economic justification for replacement method to decrease wet cooling towers makeup costs for this case study.